How does functional distinctiveness affect single species contribution to β diversity? Evidence from a subtropical forest plot in southern China. (February 2023) - Wang, Weitao; Jiang, Yun; Li, Buhang; Luo, Wenqi; Chu, Chengjin; Wang, Youshi
Highlights: Functional distinctiveness influenced SCBD indirectly through niche properties. Species niche position (OMI) and breadth (Tol) affected SCBD in opposite ways. SCBD values were lower for species with more unique trait combinations in the study plot. Abstract: To biologically interpret β diversity patterns, in terms of species characteristics, needs to quantify how each individual species contributes to overall β diversity (SCBD). However, the lack of studies linking SCBD to functional traits hinders to explore the full potential of the approach in biodiversity conservation. Here, we combined census data, species functional traits, and environmental variables from a 50-ha stem-mapped forest plot in southern China, with the aim to disentangle the relationship among SCBD, species functional traits and niche properties. We used nine functional traits to estimate species functional distinctiveness, and eleven environmental variables were used to compute species niche properties (niche position and niche breadth). Structural equation modeling (SEM) was applied to analyze how functional distinctiveness and niche properties jointly influenced SCBD. Results found that species with more unique trait combinations (higher functional distinctiveness) occupied marginal niche position and maintained smaller niche breadths and thus contributed less to overall β diversity. Meanwhile, functional distinctiveness and niche properties jointly determined SCBD. In addition, we found a negative effect of functional distinctiveness on SCBD, which implies the urgency of developing better biodiversity conservation strategies by unravelling the linkage between SCBD and ecosystem multifunctionality. These findings contribute to a better understanding of how species characteristics affect β diversity and making SCBD more applicable in biodiversity conservation.